The Influence of Motivation, Nutritional Status and Parenting Patterns on the Physical Fitness of Prospective Tennis Athletes - Husnal Petra; Damrah Damrah; Willadi Rasyid; Anton Komaini; Oyatra Utama Warda (Universitas PGRI Palembang, 2023)
The purpose of this study is to reveal the possibility of a causal relationship between variables without manipulating a variable. This type of research is quantitative using path analysis techniques (phat analysis). This research was conducted at Sijunjung 01 Public Elementary School. The population is 139 Prospective Tennis Athletes with a sample of 10-15% or 20-25% of the existing population. Data analysis techniques were carried out descriptively and interactively. Presentation of data using a frequency distribution list and histogram.The results obtained from the variables nutritional status of Prospective Tennis Athletes and Physical Fitness Prospective Tennis Athletes at SD Negeri 01 Sijunjung, there is a direct effect of nutritional status (X2) on Physical Fitness (Y) of ҏyx2 = 0.190. The variable parenting style and physical fitness has a direct effect on parenting style (X3) on physical fitness (Y) of ҏyx3 = 0.176. Calculation of path analysis, there is an indirect effect of motivation (X1) on physical fitness (Y) through parenting (X3) of 0.192. Calculation of path analysis, there is an indirect effect of nutritional status (X2) on physical fitness (Y) through parenting (X3) of 0.213. There is a simultaneous effect on motivation (X1), nutritional status (X2), parenting style (X3) and physical fitness (Y) obtained Rsquare = 0.338 or an effect of 33. Confirm to coach as a subject athletes needs a development and exercise effect nutritions.